2013
DOI: 10.1002/jbmb.32946
|View full text |Cite
|
Sign up to set email alerts
|

Thiol‐ene/acrylate substrates for softening intracortical electrodes

Abstract: Neural interfaces have traditionally been fabricated on rigid and planar substrates, including silicon and engineering thermoplastics. However, the neural tissue with which these devices interact is both 3D and highly compliant. The mechanical mismatch at the biotic-abiotic interface is expected to contribute to the tissue response that limits chronic signal recording and stimulation. In this work, novel ternary thiol-ene/acrylate polymer networks are used to create softening substrates for neural recording el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(147 citation statements)
references
References 26 publications
3
144
0
Order By: Relevance
“…While SU-8 has a relatively positive literature supporting its in vitro and in vivo biocompatibility (65), it is not typically found in implantable biomedical devices and providers (e.g., MicroChem) may be hesitant to grant use for medical applications. Nevertheless, we remain optimistic that polymers, including those with shape memory thermomechanical characteristics (66,67), offer a solution for implantable microscale devices. We note that polymeric materials including silicone, parylene, and polyamide, are all components of the Medtronic DBS Lead Model 3387.…”
Section: Introductionmentioning
confidence: 99%
“…While SU-8 has a relatively positive literature supporting its in vitro and in vivo biocompatibility (65), it is not typically found in implantable biomedical devices and providers (e.g., MicroChem) may be hesitant to grant use for medical applications. Nevertheless, we remain optimistic that polymers, including those with shape memory thermomechanical characteristics (66,67), offer a solution for implantable microscale devices. We note that polymeric materials including silicone, parylene, and polyamide, are all components of the Medtronic DBS Lead Model 3387.…”
Section: Introductionmentioning
confidence: 99%
“…the chamber reached an ultra-high vacuum of <1.0 Â 10 À7 Torr, ene reactions (click reactions). Low cure-stresses are present 204 in the final polymer due to the nature of the step-growth 205 mechanism in this polymerization, which results in highly 206 uniform/dimensionally stable polymer networks with low shrink-207age and surface roughness, as well as strong adhesion to metal lay-208 ers[18]. More significantly, this allows for various material 209 properties (such as T g , rubbery modulus and hydrophobicity)…”
mentioning
confidence: 98%
“…T g by DMA is 222 denoted by the peak of the tangent delta curve, which is shown 223 to be 43°C for this network. It has been shown that the T g of the 224 substrate will increase with increasing diacrylates mol%, but the 225 shear modulus below these transition temperatures will remain 226 relatively unchanged [18]. 227 The device structure for the OLED used in these experiments is …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over a few days, activated glia migrate to the implant site and begin to phagocytose cellular debris and damaged extracellular matrix. The accumulation of neurotoxic factors including cytokines, chemokines, and reactive oxygen species around the implant leads to a localized decrease in neuron density [Abidian et al, 2010] [Ware et al, 2014] may provide a solution to allow targeted implant insertion while reducing acute inflammation and local neuron death caused by larger and stiffer interfaces.…”
Section: Overcoming Hurdles At the Tissue Interfacementioning
confidence: 99%